COVID-19: What we know - Bittmann, Stefan (Journal of Pediatric Health And Nutrition, 2020)
A concise overview synthesizes early knowledge on COVID‑19 in pediatrics, covering transmission, clinical spectrum, diagnostics, and prevention, and pointing to priorities for longitudinal study.
Keywords: COVID-19; Transmission; Diagnostics; Prevention; Pediatrics